1991
DOI: 10.1177/000456329102800513
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Pancreatic Pro-Phospholipase A2 Activation Using an Immunoassay for the Free Activation Peptide DSGISPR

Abstract: There are several forms of the enzyme phosphoLipase A2 (PLA2) in human tissues. In the pancreas the enzyme is produced as a zymogen, pro-phospholipase A2 (pro-PLA2). The active form is generated upon proteolytic cleavage of the N-terminal prophospholipase A2 activation peptide (PLAP), with the sequence Asp-Ser-Gly-Ile-Ser-Pro-Arg (DSGISPR). Antisera specific for free PLAP were produced by immunization with the synthetic peptide, N-terminally conjugated to bovine thyroglobin. Affinity purified antibodies were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Most of the zymogen Pro-PROP released into the systemic circulation in necrotizing pancreatitis therefore seems to remain unactivated and does not play a role in the development of systemic complications. Therefore we could not substantiate the hope that plasma PROP is an early indicator of systemic complications and an important early event in the systemic response to acute pancreatitis as suggested by previous studies on urinary PROP [3, 14, 28]. There remain some questions on PROP that need to be addressed in further studies: to what extend is PROP derived from activated pancreatic PLA 2 -I or released from activated granulocytes locally as well as in the systemic circulation.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Most of the zymogen Pro-PROP released into the systemic circulation in necrotizing pancreatitis therefore seems to remain unactivated and does not play a role in the development of systemic complications. Therefore we could not substantiate the hope that plasma PROP is an early indicator of systemic complications and an important early event in the systemic response to acute pancreatitis as suggested by previous studies on urinary PROP [3, 14, 28]. There remain some questions on PROP that need to be addressed in further studies: to what extend is PROP derived from activated pancreatic PLA 2 -I or released from activated granulocytes locally as well as in the systemic circulation.…”
Section: Discussionmentioning
confidence: 71%
“…Active trypsin is difficult to measure because is it quickly complexed or denatured. Therefore, the measurement of specific peptides that are released on activation has evolved as a helpful tool in assessing zymogen activation [3, 10, 11, 14, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…PROP can be used in assays to characterize the severity of acute pancreatitis (11). The C-terminal pentapeptide of PROP (GISPR) is essential for the inhibition of enzyme activity (12). Besides trypsin, pro-hG1B can also be activated by thrombin (13) and 29-kDa trypsin-like endogenous type 1-proPLA2 activator (11).…”
mentioning
confidence: 99%
“…Phospholipase A 2 (PLA 2 ) has been investigated as a marker of MODS, 14 but a recent study showed that there was no correlation between serum PLA 2 activity and the severity of the disease, so serum pro-PLA 2 was recently proposed as an alternative. 15,16 There have been some reports dealing with the correlation between blood IL-6 or urinary trypsinogen activation peptide (TAP) and severity level. The blood concentration of IL-6 increases within 24 h after the onset of symptoms, reaching a peak value in 24-36 h; thus, discrimination of severity is possible with a sensitivity of 100% and a specificity of 71% by 24 h after hospitalization.…”
Section: Discussionmentioning
confidence: 99%